BROMOTIROSINAS DERIVADAS DE ESPONJAS MARINAS INHIBEN LA REPLICACIÓN IN VITRO DEL VIH-1 - León G GÓMEZ-ARCHILA (Universidad de Antioquia, 2014)
Background: Human immunodeficiency virus type 1 (HIV-1) infection and Acquired immunodeficiency syndrome are mayor global public health issues. HIV-1 infection is now manageable as a chronic disease thanks to the development of antiretroviral therapy; however, the existence of HIV drug resistance and collateral effects have increased the search for therapeutic alternatives. Compounds of marine resources have been studied for their antiviral potential. Objectives: To evaluate the antiviral activity of isolated bromotyrosine-derivative compounds from the Colombian marine sponges, Verongula rigida and Aiolochoria crassa against HIV-1 infection in vitro. Methods: Cytotoxicity of 11 bromotyrosine-derivative compounds was determined by the MTT assay. Inhibition of HIV-1 replication was performed using the U373-MAGI cell line, which was infected with recombinant green fluorescent protein (GFP)-expressing viruses pseudotyped, in the presence or absence of the compounds. The percentage of infected cells was evaluated by flow cytometry. In addition, the inhibition of reverse transcription and nuclear import was determined by quantification of early and late reverse transcription products and 2-LTR circles, respectively, using quantitative PCR. Results: Aeroplysinin-1, purealidin B and 3-bromo-5-hydroxy-Omethyltyrosine inhibited the HIV-1 replication in a dose-dependent manner, with a median maximum percentage of inhibition of 74% (20 μM), 57% (80 μM) and 47% (80 μM), respectively. Importantly, none of these concentrations were cytotoxic. Aeroplysinin-1, 19-deoxyfistularin 3, purealidin B, fistularin 3 and 3-bromo-5-hydroxy-O-methyltyrosine inhibited the nuclear import efficiently; while 3,5-dibromo- N,N,N,O-tetramethyltyraminium, aeroplysinin-1, purealidin B, fistularin 3 and 3-bromo-5-hydroxy-Omethyltyrosine inhibited X4 HIV-1 cell entry with a median maximum percentage of inhibition ranging between 2 to 30%. Conclusions: Aeroplysinin-1, 19-deoxyfistularin 3, purealidin B, fistularin 3 and 3-bromo-5-hydroxy-O-methyltyrosine inhibited HIV replication at different steps. This study opens the possibility of chemically synthesizing these compounds and evaluating them as alternative therapies against HIV-1.